2022
DOI: 10.3389/fendo.2022.847692
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Type 2 Diabetes and Associated Cardiometabolic Traits and Their Heritability Estimates in Endogamous Ethnic Groups of India: Findings From the INDIGENIUS Consortium

Abstract: To assess the burden of type 2 diabetes (T2D) and its genetic profile in endogamous populations of India given the paucity of data, we aimed to determine the prevalence of T2D and estimate its heritability using family-based cohorts from three distinct Endogamous Ethnic Groups (EEGs) representing Northern (Rajasthan [Agarwals: AG]) and Southern (Tamil Nadu [Chettiars: CH] and Andhra Pradesh [Reddys: RE]) states of India. For comparison, family-based data collected previously from another North Indian Punjabi S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“… 52 Population studies have revealed a historic admixture pattern mirroring a North-South gradient [Ancestral North Indians (ANI) vs. Ancestral South Indians (ASI)]. 53 , 54 , 55 A gene-flow from Europe to North India has been indicated in the manifestation of external phenotypes such as skin colour, 56 which could potentially be extended to metabolism. It could be speculated that there would be a higher degree of similarity between findings in Europe and North India whereas this would tend to reduce as one moves further South, given the increasing genetic diversity between the different geographies.…”
Section: Discussionmentioning
confidence: 99%
“… 52 Population studies have revealed a historic admixture pattern mirroring a North-South gradient [Ancestral North Indians (ANI) vs. Ancestral South Indians (ASI)]. 53 , 54 , 55 A gene-flow from Europe to North India has been indicated in the manifestation of external phenotypes such as skin colour, 56 which could potentially be extended to metabolism. It could be speculated that there would be a higher degree of similarity between findings in Europe and North India whereas this would tend to reduce as one moves further South, given the increasing genetic diversity between the different geographies.…”
Section: Discussionmentioning
confidence: 99%
“…In the same year, Saxena et al [ 44 ] published a study on the Punjabi Sikh population with a novel signal at the SGCG gene. Recently, a study [ 45 ] published on the genetic basis of T2D in three ethnically endogamous Indian populations based in Tamil Nadu, Rajasthan and Andhra Pradesh states (the INDIGENIUS Consortium) also demonstrated substantial population-specificity in the genetic basis of T2D within Indian populations. It is therefore a need to conduct T2D GWAS studies in ethnically coherent subgroups within India.…”
Section: Discussionmentioning
confidence: 99%
“…The Indian population exhibits unique characteristics, such as a higher prevalence of insulin resistance, a distinct genetic profile, and disparities in healthcare access and quality. These unique characteristics of the Indian population make it imperative to evaluate the efficacy and safety of anti-diabetic agents in this population [9]. Furthermore, T2DM is often associated with comorbidities such as obesity, dyslipidemia, and hypertension, which further complicate management and may require multiple therapeutic interventions [10].…”
Section: Introductionmentioning
confidence: 99%